Attitude Competency Assessment in the 2013 curriculum based on elementary school Prototyping methods - Febriyanto, Erick; Naufal, Romzi Syauqi; budiarty, frizca (Pandawan Sejahtera Indonesia, 2019)
In the rapid development of 4.0 technology, now all aspects and types of activities have begun to utilize the presence of increasingly sophisticated technology to facilitate the activities, including the utilization of technology in the world of education. However, the application of technology in primary schools has not been able to be used properly, one of them in supporting the government program is 2013 curriculum. Based on the observation done at SDN Sukanagara and the study of the literature, in the process of processing competency values of students ' social and spiritual attitude is still less efficient, because assessment and input value still use the method Conventional time consuming and using a lot of paper on its process. In an effort to support the paperless program, utilization of technology for Attitude Competency Assessment in 2013 curriculum is needed, so there needs to be a system that can facilitate the assessment process of attitude competency that is more concise, efficient and Paperless. In this study there are 3 (three) methods used: Observation, library study, and prototyping. The results of this research in the form of prototype input competency assessment of social and spiritual attitude is packaged in the form of questionnaire, which is expected to assist in the processing of assessment data.